To solve this we are going to use the exponential function: [tex]f(t)=a(1(+/-)b)^t[/tex]
where
[tex]f(t)[/tex] is the final amount after [tex]t[/tex] years
[tex]a[/tex] is the initial amount
[tex]b[/tex] is the decay or grow rate rate in decimal form
[tex]t[/tex] is the time in years
Expression A
[tex]f(t)=624(0.95)^{4t}[/tex]
Since the base (0.95) is less than one, we have a decay rate here.
Now to find the rate [tex]b[/tex], we are going to use the formula: [tex]b=|1-base|[/tex]*100%
[tex]b=|1-0.95|[/tex]*100%
[tex]b=0.05[/tex]*100%
[tex]b=[/tex]5%
We can conclude that expression A decays at a rate of 5% every three months.
Now, to find the initial value of the function, we are going to evaluate the function at [tex]t=0[/tex]
[tex]f(t)=624(0.95)^{4t}[/tex]
[tex]f(0)=624(0.95)^{0t}[/tex]
[tex]f(0)=624(0.95)^{0}[/tex]
[tex]f(0)=624(1)[/tex]
[tex]f(0)=624[/tex]
We can conclude that the initial value of expression A is 624.
Expression B
[tex]f(t)=725(1.12)^{3t}[/tex]
Since the base (1.12) is greater than 1, we have a growth rate here.
To find the rate, we are going to use the same equation as before:
[tex]b=|1-base|[/tex]*100%
[tex]b=|1-1.12|[/tex]*100
[tex]b=|-0.12|[/tex]*100%
[tex]b=0.12[/tex]*100%
[tex]b=[/tex]12%
We can conclude that expression B grows at a rate of 12% every 4 months.
Just like before, to find the initial value of the expression, we are going to evaluate it at [tex]t=0[/tex]
[tex]f(t)=725(1.12)^{3t}[/tex]
[tex]f(0)=725(1.12)^{0t}[/tex]
[tex]f(0)=725(1.12)^{0}[/tex]
[tex]f(0)=725(1)[/tex]
[tex]f(0)=725[/tex]
The initial value of expression B is 725.
We can conclude that you should select the statements:
- Expression A decays at a rate of 5% every three months, while expression B grows at a rate of 12% every fourth months.
- Expression A has an initial value of 624, while expression B has an initial value of 725.